A feasibility study on low enriched uranium fuel for nuclear thermal rockets – II: Rocket and reactor performance. (March 2016) - Venneri, Paolo F.; Kim, Yonghee
Abstract: This paper is the second paper on the study regarding the feasibility of low-enriched uranium (LEU) fuel in nuclear thermal rocket (NTR) applications. While the first paper dealt primarily with the issue of achieving and demonstrating criticality of the LEU-loaded NTR, this companion paper addresses other important reactor parameters which need to be verified in order to demonstrate the practicability of the LEU-NTR. Following the conclusions of the first paper, this second paper seeks to characterize various neutronic and performance parameters in order to definitely demonstrate the technical feasibility of the LEU-NTR. The parameters characterized and presented in this study are the reactor burn-up behavior including effects due to the build-up of Xe-135, the temperature coefficient of reactivity, the reactivity capability of the control drum system, and a rocket performance comparison with previous NTR systems. Impacts of the transient Xe reactivity change during operation have been characterized though various reactor depletion analyses using the MCNP5.1 and MCNPX codes in combination with the ENDF/B-VII.0 nuclear data library. The necessary level of excess reactivity of the LEU-loaded reactor has been quantified and the reactivity control drum, system has been assessed in term of the reactor shutdown capability. In this work, the reference core design presented in the first paper has been modified in order to improve the operational performance of the LEU-NTR to operate with a 900 s specific impulse and a 110 kN thrust. Highlights: Presents an LEU-NTR which satisfies the NASA DRA 5.0 mission requirements. Determines the need for power profile flattening. Characterizes the general neutronic characteristics of the core. Compares the performance of the LEU-NTR with previous HEU-NTR designs.